Cost-Effectiveness of Avelumab Maintenance Therapy Plus Best Supportive Care vs. Best Supportive Care Alone for Advanced or Metastatic Urothelial Carcinoma - Xie, Qian; Zheng, Hanrui; Chen, Ye; Peng, Xingchen (Frontiers in Public Health, 2022)
Objective To our knowledge, there is no relevant economic analysis about avelumab maintenance therapy for advanced or mUC worldwide, so we conducted this study to evaluate the cost-effectiveness of avelumab maintenance therapy for advanced or mUC from the perspective of the US payer. Avelumab (MSB0010718C) is a fully human anti programmed cell death ligand 1(PD-L1) antibody against PD-L1 interactions and enhances immune activation against tumor cells in the meantime. Avelumab has been approved for Locally Advanced or mUC after disease progression in several countries. Methods A Markov simulation model was performed based on clinical trial JAVELIN Bladder 100. Two simulated treatment included avelumab maintenance therapy group (AVE group) and best supportive care group (CON group). Utilities and costs adopted in this analysis were derived from published literature and clinic trials. Incremental cost-effectiveness ratios (ICERs) were calculated to compare the two treatments. In the sensitivity analysis part, deterministic sensitivity analysis (DSA) and probabilistic sensitivity analysis (PSA) were considered. Results While in the PD-L1–positive population, the AVE group gained 0.07 QALYs more than patients in the CON group. The ICER of AVE group compared with CON group were 19,962.00 USD and 12,071.71 USD per QALYs in the overall population and in the PD-L1–positive population, respectively. Conclusion The results suggest that first-line maintenance avelumab therapy is cost-effective not only in the PD-L1–positive population but also in the overall population base on the current WTP of 150000 USD in the US.